Presentation and Surgical Management of Duodenal Duplication in Adults. (30th December 2015) - Jadlowiec, Caroline C.; Lobel, Beata E.; Akolkar, Namita; Bourque, Michael D.; Devers, Thomas J.; McFadden, David W.
Abstract : Duodenal duplications in adults are exceedingly rare and their diagnosis remains difficult as symptoms are largely nonspecific. Clinical presentations include pancreatitis, biliary obstruction, gastrointestinal bleeding from ectopic gastric mucosa, and malignancy. A case of duodenal duplication in a 59-year-old female is presented, and her treatment course is reviewed with description of combined surgical and endoscopic approach to repair, along with a review of historic and current recommendations for management. Traditionally, gastrointestinal duplications have been treated with surgical resection; however, for duodenal duplications, the anatomic proximity to the biliopancreatic ampulla makes surgical management challenging. Recently, advances in endoscopy have improved the clinical success of cystic intraluminal duodenal duplications. Despite these advances, surgical resection is still recommended for extraluminal tubular duplications although combined techniques may be necessary for long tubular duplications. For duodenal duplications, a combined approach of partial excision combined with mucosal stripping may offer advantage.